Pengaruh Kecurangan Laporan Keuangan terhadap Nilai Perusahaan: Ditinjau dari Perspektif Fraud Pentagon (Kasus di Indonesia) - Desi Elviani; Syahril Ali; Rahmat Kurniawan (Universitas Batanghari Jambi, 2020)
This study aims to examine how the influence of fraudulent financial reporting on firm value is viewed from the perspective of a pentagon fraud with a sample of 71 companies from the infrastructure, utilities and transportation sectors in the Indonesia Stock Exchange in 2014-2018. The sample selection used was purposive sampling method. Company value is measured by price book value, financial statement fraud is measured by fraud-score models. There are two variables that have a positive and significant influence, namely the opportunity and arrogance variables, the two variables present two of the five elements of pentagon fraud, where as the three variables, pressure, rasionalization, competence, do not affect the fraudulent financial reporting. The results of this study have proven that fraudulent financial reporting has a negative effect on firm value.